A global survey to understand general vaccine trust, COVID-19 and influenza vaccine confidence - D’Silva, Chelsea; Fullerton, Madison M.; Hu, Jia; Rabin, Kenneth; Ratzan, Scott C. (Frontiers in Public Health, 2024)
IntroductionThe COVID-19 pandemic has greatly impacted the way that the world views vaccines. While safe and effective, COVID-19 vaccines were, and continue to be met with hesitancy and misinformation. We aimed to understand public perceptions and trust in COVID-19 vaccinations and how the pandemic has impacted perceptions of non-COVID-19 vaccines.MethodsSurvey data were collected between August 7, 2023–August 16, 2023, from 7,000 respondents aged 18 years and older from the United States (n = 1,000); Nigeria (n = 1,000); United Kingdom (n = 1,000); France (n = 1,000); Canada (n = 1,000); Brazil (n = 1,000); and India (n = 1,000).ResultsTrust in COVID-19 vaccines was highest in Brazil (84.6%) and India (80.4%) and lowest in the United States (63.5%) and France (55.0%). 47.5% of respondents agreed that they trust traditional protein-based vaccines more than mRNA vaccines, 13.5% disagree and 39.0% are neutral about their trust in protein-based versus mRNA vaccines. Overall, 53.9% of respondents reported that the COVID-19 pandemic impacted their perceptions of vaccines with half of these respondents (51.7%) reporting that the pandemic made them think that other vaccines are more important as they understand how critical vaccines can be at preventing serious illnesses.DiscussionThese data can be used by health system decision makers, public health and researchers to understand how vaccine trust impacts perceptions of COVID-19 and influenza vaccines globally and develop tailored interventions that address local concerns.